Harnessing Uzbekistan potential of Urbanization national urban assessment. (Country sector and thematic assessments., 2021)
In terms of sustainable urbanization, particular focus is given on economy, equity, environmental quality, and climate change as well as enhancing the quality and reliability of urban services and increasing the supply of affordable housing, among others. The report is also a useful guide for strategic investment planning across key urban infrastructure sectors in Uzbekistan.